2007
DOI: 10.1068/p5441
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Early-Blind, Late-Blind, and Blindfolded-Sighted People in Haptic Spatial-Configuration Learning and Resulting Memory Traces

Abstract: The roles of visual and haptic experience in different aspects of haptic processing of objects in peripersonal space are examined. In three trials, early-blind, late-blind, and blindfolded-sighted individuals had to match ten shapes haptically to the cut-outs in a board as fast as possible. Both blind groups were much faster than the sighted in all three trials. All three groups improved considerably from trial to trial. In particular, the sighted group showed a strong improvement from the first to the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
94
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 32 publications
10
94
0
3
Order By: Relevance
“…This could also be explained by their enhanced haptic-tactile acuity (Postma et al 2007;Wolbers et al 2005). The stable, high coherence (also before the active tactile stimulus) in sighted subjects, instead, suggests a continuous, high information flow, possibly related to memory and mental mapping (Engel and Fries 2010).…”
Section: Objective and Subjective Parametersmentioning
confidence: 99%
“…This could also be explained by their enhanced haptic-tactile acuity (Postma et al 2007;Wolbers et al 2005). The stable, high coherence (also before the active tactile stimulus) in sighted subjects, instead, suggests a continuous, high information flow, possibly related to memory and mental mapping (Engel and Fries 2010).…”
Section: Objective and Subjective Parametersmentioning
confidence: 99%
“…Interestingly, our data show that the strategy used to encode the tactile pictures highly depends on age at onset of blindness and on the proportion of life-time without visual experience. Previous reports have shown that mental imagery varies according to age at onset of blindness [14,15]. Our study is the first study to reveal the precise interplay between strategy use and the proportion of life-time without visual experience, a parameter (P) that is worth assessing and/or controlling in studies involving totally blind participants.…”
Section: Discussionmentioning
confidence: 91%
“…Participants have congenital blindness (2 of 8) or are early blind (6 of 8), a condition that requires the use of a screen reader to access digital information. As one of the participants stated "blind people are not an homogeneous population" and there are differences, for instance, with respect to spatial perception between early and late blind [14]. Since it would not have been possible, at this stage, to isolate this condition, we recruited the subjects in order to have a sample as uniform as possible.…”
Section: User Studymentioning
confidence: 99%